Effect of the Suryanamaskar in the management of Dyslipidemia: A clinical study - Arya, Jaideep; Bora, Manju (International Research Journal of Ayurveda & Yoga, 2023)
The purpose of the study was to find out the effect of Surya namaskar on the management of Dyslipidemia patients. To achieve this purpose, sixty (N=60) patients with Dyslipidemia were selected from Bhiwani, Haryana with their ages ranging between 21 to 57 years. They were classified into two groups i.e.; one is the control group (N=30) (Medicine + No change in their daily routine) and the other is an experimental or interventional group (N=30) (Medicine + Suryanamaskar practice 30±10 minutes/day for 5 days/week over the period of twelve weeks). Suryanamskar was assessed for all the selected subjects by an expert Yoga trainer doing an intervention programme, and the Dyslipidemia was examined by the level of Cholesterol, level of triglycerides, level of high-density Lipoprotein-s, and level of very low-density Lipoprotein-s test before and after the intervention programme and collected data were subjected to statistical treatment by using SPSS (Statistical Package of Social Sciences, version 20). In all the cases 0.05 level of confidence was fixed to test the significance. After that, in the concluding phase, the result has become significant, that depict, the Suryanamaskar training shows better improvement in the management of Dyslipidemia.